Fabrication of Metal–Organic Framework-Mediated Heterogeneous Photocatalyst Using Sludge Generated in the Classical Fenton Process - Xiang-Yu Wang; Xu Liu; Wu Kuang; Hong-Bin Xiong (Nanomaterials)
The sludge produced by the Fenton process contains mixed-valence iron particulates (hereafter called Fenton wastes). Using a solvothermal method, we fabricated a new heterogeneous photo-Fenton catalyst using Fenton wastes and metal–organic frameworks (MOFs). Nanoporous metal carboxylate (MIL-88) MOF impregnated with Fenton waste was functionalized using 2,5-dihydroxyterephthalic acid (x-HO-MIL-88-C, x, concentration of the 2,5-dihydroxyterephthalic acid). The efficiency of x-HO-MIL-88-C was examined under visible light radiation using methylene blue (MB) as an index pollutant. We observed the best catalytic performance for MB degradation by 4-HO-MIL-88-C. In the photo-Fenton process, the simultaneous presence of singlet oxygen, superoxide, and hydroxyl radicals is confirmed by free radical quenching and electron spin resonance spectral data. These free radicals associate with holes in the non-selective degradation of MB. The 4-HO-MIL-88-C catalyst shows good stability and reusability, maintaining over 80% efficiency at the end of five consecutive cycles. This work opens up a new path for recycling Fenton wastes into usable products.